Analysis and measurement of dielectrophoretic manipulation of particles and lymphocytes using rail-type electrodes. Issue 1 (January 2016) - Tatsumi, K.; Kawano, K.; Okui, H.; Shintani, H.; Nakabe, K.
Highlights: Numerical models for dielectrophoretic force extracted on particles and nucleated cells in microchannels were evaluated using rail-type electrodes. We confirmed that the higher order terms of the electric field intensity distributions and the electric interaction of the static charge and polarization becomes noticeable for nucleated cells in microchannel flows. The force density model showed the highest performance while CM function showed a 70% deviation from the measurement. The ladder-type electrodes presented can align the particle with even spacing in the streamwise direction. By combining the ladder-type electrodes and flip-type electrodes, the sorting performance was markedly improved. Abstract: A particle manipulation and sorting device using the dielectrophoretic (DEP) force is described in this study. The device consists of "ladder-type", "flip-type" and "oblique rail-type" electrode regions. The ladder-type and rail-type electrodes can generate a DEP force distribution that captures the particles, the DEP force of which is negative, in the area located at the center of the electrodes. The ladder-type electrode can align the particles with equal spacing in the streamwise direction. Using the flip-type electrode, which pushes the particles away, in combination with these electrodes, the direction of the particle and timing can be selected with high accuracy, reliability, and response. In the first half of this study, a numerical simulation is carried out to calculate the particle motion and evaluate the performance of the ladder-type electrode. Several models are used to investigate the influences of the non-uniformity of the electric field and the electric interaction of the surface charges and polarizations. Experiments are then carried out to demonstrate the motions of the particles and the sorting reliability. The trajectories and the probability density functions of the particles at the inlet and outlet of the electrode region showed that by using these electrodes the particles can be aligned, sorted, and guided accurately.